Influence Analysis Of Forced Distribution Rating Performance Appraisal And Merit Pay To Performance Of Directorate General Of Taxes’s Employees With Job Satisfaction As Intervening Variable At Blora Tax Service Office - Mirwan Surya Perdhana; Zainur Hidayah; Sigit Fadhil Rais - (IJHCM (International Journal of Human Capital Management), 2021)
This study aims to analyze and determine influence of forced distribution rating performance appraisal and merit pay toward performance of Directorate General of Taxes’s employees with job satisfaction as intervening variable at Blora Tax Service Office. Technique used for this study is census then data analyzed with SmartPLS. This research’s subjects are 80 low management employees at Blora Tax Service Office. The result of this research shows that forced distribution rating performance appraisal and merit pay don’t affect directly on employee’s performance. But forced distribution rating performance appraisal and merit pay have positive and significant effect on job satisfaction while job satisfaction has positive and significant effect on performance. Then indirectly through job satisfaction, forced distribution rating performance appraisal and merit pay have positive and significant effect to employee’s performance. This result shows that job satisfaction is a suitable intervening variable for this research. Based on this research, it is suggested for future managerial policy with goal to increase performance, job satisfaction should be one of deciding factors.